The first transcriptome sequencing and data analysis of the Javan mahseer (Tor tambra) - Lau, Melinda Mei Lin; Lim, Leonard Whye Kit; Chung, Hung Hui; Gan, Han Ming (Elsevier Inc., 2021)
The Javan mahseer ( Tor tambra ) is one of the most valu- able freshwater fish found in Tor species. To date, other than mitogenomic data (BioProject: PRJNA422829), genomic and transcriptomic resources for this species are still lack- ing which is crucial to understand the molecular mechanisms associated with important traits such as growth, immune response, reproduction and sex determination. For the first time, we sequenced the transcriptome from a whole juve- nile fish using Illumina NovaSEQ60 0 0 generating raw paired- end reads. De novo transcriptome assembly generated a draft transcriptome (BUSCO5 completeness of 91.2% [Actinoptery- gii_odb10 database]) consisting of 259,403 putative tran- scripts with a total and N50 length of 333,881,215 bp and 2283 bp, respectively. A total count of 77,503 non-redundant protein coding sequences were predicted from the transcripts and used for functional annotation. We mapped the pre- dicted proteins to 304 known KEGG pathways with signal transduction cluster having the highest representation fol- lowed by immune system and endocrine system. In addi- tion, transcripts exhibiting significant similarity to previously published growth-and immune-related genes were identified which will facilitate future molecular breeding of Tor tambra .